2018
DOI: 10.1007/s00705-018-3987-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a conserved neutralizing epitope in the G-protein of Chandipura virus

Abstract: Chandipura virus (CHPV), associated with an encephalitic illness in humans, has caused multiple outbreaks with high mortality in central and western India in recent years. The present study compares surface glycoprotein (G-protein) from prototype and recent outbreak strains using in silico tools and in vitro experiments. In silico epitope predictions (B-cell and T-helper cell) for the sequences, 3D structure prediction and comparison of the G-proteins of the strains: I653514 (Year 1965), CIN0327 (Year 2003) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Bioinformatics plays important role in immunological studies and viral diagnostics like the design of ELISA based tests, chimeric peptides, antigen-antibody interactions, etc . ( Gangwar et al, 2011 ; Gangwar et al, 2012 ; Shil, Chavan & Cherian, 2011a ; Shil, Chavan & Cherian, 2011b ; Pavitrakar et al, 2018 ; Pavitrakar et al, 2020 ) . Hence, quick and easy data retrieval from databases is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics plays important role in immunological studies and viral diagnostics like the design of ELISA based tests, chimeric peptides, antigen-antibody interactions, etc . ( Gangwar et al, 2011 ; Gangwar et al, 2012 ; Shil, Chavan & Cherian, 2011a ; Shil, Chavan & Cherian, 2011b ; Pavitrakar et al, 2018 ; Pavitrakar et al, 2020 ) . Hence, quick and easy data retrieval from databases is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics plays important role in immunological studies and viral diagnostics like design of ELISA based tests, chimeric peptides, antigen-antibody interactions, etc (Gangwar et al, 2012;Gangwar et al, 2011;Shil et al, 2011b;Shil et al, 2011a;Pavitrakar et al, 2018;Pavitrakar et al, 2020). Hence, quick and easy data retrieval from databases is essential.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid sequence of CHPV G protein shares a 40% identity and 65% similarity with VSV G protein (Masters et al, 1989). The comparison study between different strains of CHPV associated with past outbreaks revealed that CHPV G protein is stable and its antigenic determinants are conserved (Pavitrakar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%